(untitled) (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
This work provides an explanation, describes the principle of operation and determines the main purpose of systems that provide the surface of the field with harvesting agricultural machines. The analysis of existing balancing mechanisms and copying systems used in agricultural structures for harvesting has been analyzed, with an emphasis on their strengths and weaknesses. According to the results of the analysis of different designs of copying systems, their classification is proposed and explained how they are structurally related, which allows to give a general characteristic of these systems.